The Innovation Intermediaries Role in the Adoption of Emerging Technologies in Iran's Automotive Industry - Ali Maleki; Hadi Nilforoushan (مدیریت صنعتی)
Objective The success rate of a type of technology is manifested in its adoption and continued use. In this sense, the condition development, user behavior, and the factors affecting it should be identified. However, this issue has been almost neglected and most of the studies only examined the factors influencing the adoption and use of technology at a particular time. Over the last two decades, scientific research has notably focused on the adoption of theories of emerging technologies within information and industrial systems. Innovation intermediaries are organizations or bodies that act as representatives or agents in every aspect of the innovation process between two parties and are recognized as important actors that can facilitate the innovation process. The combination of these two with the embargoes governing Iran’s industrial environment, imposed with different intentions, has led this research to investigate the effect of innovation Intermediaries on the adoption of emerging technologies in the automotive industry with the moderating role of embargo restrictions.